2010
DOI: 10.1111/j.1365-2958.2009.07024.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the superoxide dismutase family in Aspergillus fumigatus

Abstract: SummaryReactive oxidant species produced by phagocytes have been reported as being involved in the killing of Aspergillus fumigatus. Fungal superoxide dismutases (SODs) that detoxify superoxide anions could be putative virulence factors for this opportunistic pathogen. Four genes encoding putative Sods have been identified in the A. fumigatus genome: a cytoplasmic Cu/ZnSOD (AfSod1p), a mitochondrial MnSOD (AfSod2p), a cytoplasmic MnSOD (AfSod3p) and AfSod4 displaying a MnSOD C-terminal domain. During growth, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
163
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(183 citation statements)
references
References 70 publications
9
163
1
10
Order By: Relevance
“…In this study, we identified a role for the superoxide dismutases in mediating hyphal survival during oxidation by neutrophils and during infection. Our findings are consistent with increased cytoplasmic SOD1 and SOD3 but not mitochondrial SOD2 expression by A. fumigatus hyphae in the presence of normal versus CGD neutrophils (72) and the increased susceptibility of A. fumigatus Δsod1/2/3 mutants to killing by alveolar macrophages (37). However, Δsod1/2/3 mutants showed no difference in survival in an immunocompromised lung infection model (37).…”
Section: Figure 10supporting
confidence: 78%
See 2 more Smart Citations
“…In this study, we identified a role for the superoxide dismutases in mediating hyphal survival during oxidation by neutrophils and during infection. Our findings are consistent with increased cytoplasmic SOD1 and SOD3 but not mitochondrial SOD2 expression by A. fumigatus hyphae in the presence of normal versus CGD neutrophils (72) and the increased susceptibility of A. fumigatus Δsod1/2/3 mutants to killing by alveolar macrophages (37). However, Δsod1/2/3 mutants showed no difference in survival in an immunocompromised lung infection model (37).…”
Section: Figure 10supporting
confidence: 78%
“…Figure 10 also illustrates that A. fumigatus produces 3 superoxide dismutases that catalyze the conversion of superoxide to H 2 O 2 (37,38). SOD1 and SOD3 are both cytoplasmic, whereas SOD2 is restricted to the mitochondrial membrane (37). In this study, we identified a role for the superoxide dismutases in mediating hyphal survival during oxidation by neutrophils and during infection.…”
Section: Figure 10mentioning
confidence: 70%
See 1 more Smart Citation
“…The Cu/Zn (SOD) gene from Cordeceps militaris with a deduced 154 amino acids that shows 72-95% sequence similarities to Cu/Zn (SOD) from other fungi has been described earlier [24]. Four SOD genes in the genome of the A. fumigates have been reported and proteins of these genes provide protection to the organisms against oxidative stress [25]. PTMs are means of important mechanisms for the proper functioning of proteins [26].…”
Section: Discussionmentioning
confidence: 99%
“…The role of AfuMGTC in A. fumigatus pathogenicity was investigated as described previously by Lambou et al (18). No significant difference was seen in the survival rates of cohorts of 10 mice infected intranasally at 10 5 conidia/mouse with the parental strain, the mgtc mutant, and the complemented mgtc mutant strain.…”
mentioning
confidence: 99%